Fitness and fatness in relation with attention capacity in European adolescents: The HELENA study. Issue 4 (April 2017) - Cadenas-Sanchez, Cristina; Vanhelst, Jeremy; Ruiz, Jonatan R.; Castillo-Gualda, Ruth; Libuda, Lars; Labayen, Idoia; De Miguel-Etayo, Pilar; Marcos, Ascensión; Molnár, Eszter; Catena, Andrés; Moreno, Luis A.; Sjöström, Michael; et al.
Abstract: Objectives: To examine the association of health-related physical fitness components and accurate measures of fatness with attention in European adolescents. Design: Cross-sectional study. Methods: A sub-sample of 444 adolescents from the HELENA study (14.5 ± 1.2 years) from 6 different countries participated in this study. Adolescents underwent evaluations of fitness (20 m shuttle run, handgrip strength, standing long jump and 4 × 10 m shuttle run tests), fatness (body mass index, skinfold thicknesses, bioelectrical impedance, Bod Pod and dual-energy X-ray absorptiometry) and attention (d2-test). Results: Higher cardiorespiratory fitness was positively associated with better attention capacity ( β = 0.1, p = 0.03). Body mass index and fat mass index measured by Bod Pod and dual-energy X-ray absorptiometry in a subset were negatively associated with attention ( β = −0.11, p = 0.02; β = −0.36, p = 0.02; β = −0.34, p = 0.03; respectively). All models were adjusted for age, sex, family-affluence scale and mother education. When these models were additionally adjusted for cardiorespiratory fitness when fatness was the main predictor and vice versa, the associations were somewhat attenuated and were no longer statistically significant. Muscular strength, speed-agility and body fatness markers measured by bioelectrical impedance and skinfolds were not associated with attention. The fit and non-overweight adolescents presented the highest values of attention capacity whilst their unfit and overweight peers showed the lowest values of attention (47.31 ± 2.34 vs. 33.74 ± 4.39; p < 0.01). Conclusions: Our results support that both cardiorespiratory fitness and fatness are associated with attention, yet these associations are not independent. A combined effect was also observed, with fit and non-overweight adolescents showing the highest levels of attention and those unfit and overweight the lowest.